1989
DOI: 10.1037/0022-0167.36.2.223
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of the Working Alliance Inventory.

Abstract: Present stages of development and preliminary validation of a self-report instrument for measuring the quality of alliance, the Working Alliance Inventory (WAI). The measure is based on Bordin's (1980) pantheoretical, tripartite (bonds, goals, and tasks) conceptualization of the alliance. Results from three studies were used to investigate the instrument's reliability and validity and the relations among the WAI scales. The data suggest that the WAI has adequate reliability. The instrument is reliably correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

49
2,864
5
96

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,098 publications
(3,014 citation statements)
references
References 43 publications
49
2,864
5
96
Order By: Relevance
“…We were interested in the question of whether patients could also build a therapeutic relationship with more than one therapist. To answer this question, following the final treatment session, all patients filled in the Working Alliance Inventory (WAI), short version (Horvath & Greenberg, 1989; Tracey & Kokotovic, 1989), a commonly used and reliable scale to measure the quality of the therapeutic relationship operationalized as the working alliance. Because more than one therapist was involved in the treatment, for each of the 12 items we replaced the word ‘therapist’ with ‘therapist team’.…”
Section: Examplementioning
confidence: 99%
“…We were interested in the question of whether patients could also build a therapeutic relationship with more than one therapist. To answer this question, following the final treatment session, all patients filled in the Working Alliance Inventory (WAI), short version (Horvath & Greenberg, 1989; Tracey & Kokotovic, 1989), a commonly used and reliable scale to measure the quality of the therapeutic relationship operationalized as the working alliance. Because more than one therapist was involved in the treatment, for each of the 12 items we replaced the word ‘therapist’ with ‘therapist team’.…”
Section: Examplementioning
confidence: 99%
“…Working Alliance Inventory (WAI; Horvath and Greenberg, 1989): The WAI is a 36-item selfreport questionnaire comprising 3 subscales of 12 items each, with respondents rating their level of agreement to statements using a 7-point Likert-like scale. The subscales assess the goals of therapy, the tasks of therapy, and the bond that develops between the clinician and patient.…”
Section: Assessmentsmentioning
confidence: 99%
“…The range of the total scores is from 36 to 252 with higher scores indicating greater therapeutic alliance. The WAI is the most widely used assessment for measuring the therapeutic alliance (Fenton et al, 2001), has well established reliability and validity (Hanson et al, 2002;Horvath and Greenberg, 1989), and has parallel forms for clinicians and patients. In the current study the WAI was administered after the third week post-randomization visit in each condition.…”
Section: Assessmentsmentioning
confidence: 99%
“…Each item is rated on a 7-point scale (1=never, 7=always). Research has shown strong support for the reliability of the WAI, ranging from α=.85 to .93 (Horvath & Greenberg, 1989). This study used a modified version of the WAI to capture the participants' perspective on the alliance in a one-time group workshop.…”
Section: Attributions-thementioning
confidence: 99%